Learner agency of immigrant pupils in a Finnish complementary language classroom context - Sun, Dukkeum (2019)
This research project starts with a simple but significant need for the exploration of the true meaning of the learners’ act for the sake of better learning and negotiation of their identity as social beings in a second classroom context. A successful language teaching is realized not only when a teacher maximizes the learners’ performance on the target language with well-woven syllabus and material but more importantly when he/she senses the ongoing appearance of the language learners’ identities in the daily classroom context in a keen manner. The present study was designed to explore the young language learners’ agency through which they become complete independent thinkers and decision makers to act to make a sense of meaning of all the potential resources within the language classroom context. To be more specific, it intends to investigate how the young learners act through their identity-agency, which is one’s own willingness to use the possible affordances to develop their identities as language learners. The initial orientation of the design of this study was realized by a bottom-up observation and analysis on the circulative process of the multilingual young learners’ development of identities and their exertion of the identity-agency through the interpretative phenomenological approach.